Human Immunodeficiency Virus disease and cardiac surgery – where are we? - Blyth, David (SA Heart Journal, 2017)
Uncertainties concerning the effects of cardiopulmonary bypass, outcome and possibility of operator injury slowed progress in cardiac surgery in the HIV-infected patient. Severely ill patients, some with AIDS and others probably with AIDS, formed the basis of early reports; it was shown they could be taken through surgery satisfactorily. Following the advent of antiretroviral monotherapy – zidovudine, an NRTI – in 1987, and dual therapy in the early 1990s with NRTIs, the addition of protease inhibitors (PI) in 1995, although a double-edged sword, led to triple therapy/HAART, (2 NRTIs and a PI) and startling improvement in morbidity and mortality in markedly compromised HIV patients. Yet, it was only in 2003 when sizeable reports carrying ARV usage began to emerge. Intravenous drug addiction causing left-sided valvular heart disease was initially responsible for most cases, but there was now an increase in coronary artery disease (CAD) in young patients, blamed partly on lipid disturbances caused by PI. With an ARV rollout in South Africa delayed to 2004, and PIs only used in second line therapy in State-administered treatment, the increase in coronary artery disease has not been noted. The need for surgery in pericardial disease is rare. Paediatric cardiac surgery has been rarely reported, but is locally carried out; a new approach to medical management of these children should lead to more frequent surgery. Heart transplantation lags far behind solid organ transplantation, but there are indications that it will be more readily accepted. Certain vascular pathologies appear to be peculiar to HIV, with the virus itself being able to enter vessel walls with evolution of vascular disease. PIs would appear to accelerate coronary artery disease, as seen in younger HIV patients, who develop abnormal lipid profi les. The approach to cardiac surgery in most cardiac teaching units is looked at. Many answers have been found, but new issues have also arisen, as in relation to ARV’s and CAD. Most importantly, attitudes are changing: some would accept selected patients with AIDS not receiving ARVs. Very good results have followed surgery in patients who have suffered AIDS defining conditions but are stable on ARVs.